Effects of Biofertilizer Formulation Dose onPhytoplankton Abundancein Peat Soil Medias of Channa Fish (Channa sp.) Culture - Yusnita, Sri; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted in January to March, 2017 the located in Kualu Nenas village, Tambang Subdistrict, Kampar District, Riau Province. Phytoplankton analyzed was conducted in Environmental Quality Laboratory of Cultivation, Faculty of Fisheries and Marine University of Riau. Method this research using a Complete Randomized Design (CRD) was one factor with 5 levels of treatments. The kinds of treatments P0 (Without gived Biofertilizer formulation (control), P1(Givedthe 300 g/m2Biofertilizer formulation), P2: (Givedthe 450 g/m2Biofertilizer formulation), P3: (Givedthe 600 g/m2Biofertilizer formulation), P4: (Givedthe 750 g/m2Biofertilizer formulation). The Biofertilizer formulation effect toabundance of phytoplankton,and the best treatment to increasing the phytoplankton abundance was dose of 750 g/m2 (P4). The abundance of phytoplankton was highly of P4 (750 g/m2) were 41,053 cells.L-1. The result of water quality parameters analyzed that the were goodly, especially of temperature 26-30oC, pH 6-8, DO 5,36 mg/L, CO2 21,00 mg/L, Nitrate 2,94 mg/L, Orthoposphate 3,28 mg/L, namely the growth of absolute weight of 8,49 g, specific growth rate of 5,58% and survival of 75% refering for theQuality Standart of Aquaculture. Keywords: Bioferlizer, Phytoplankton, Peat soil, Channa fish (Channa sp.)